A Dual Role of Content Marketing in Linking Brand Awareness and Product Quality to Purchase Intention - Novianty, Triyanisa; Faruqi, Faris; Hendryadi, Hendryadi (Jurnal Orientasi Bisnis dan Entrepreneurship (JOBS), 2025)
This study examines the effects of brand awareness and product quality on purchase intention, with content marketing acting as both a mediating and moderating variable. The research was conducted at Tuku Coffee Cempaka Putih, a well-known coffee brand among Generation Z consumers. Using a quantitative approach, data were collected from 381 respondents through purposive sampling and analyzed with Jamovi 2.6.19. The findings reveal that brand awareness and product quality have positive and statistically significant direct effects on purchase intention. Content marketing plays a dual role by significantly mediating and strengthening the relationship between brand awareness, product quality, and purchase intention, with medium-to-strong effect sizes. These results indicate that effective social media–based content marketing enhances brand recall and perceived product quality while amplifying their influence on consumers’ purchase intentions. The novelty of this study lies in demonstrating the simultaneous mediating and moderating roles of content marketing within a single empirical model, particularly among Generation Z consumers in the coffee retail industry. Practically, the findings offer valuable insights for brand managers, digital marketers, and SME owners in developing strategic content marketing to strengthen brand positioning, expand market reach, and build long-term customer loyalty